PENGARUH MEDIA SOSIAL TERHADAP PERILAKU KONSUMEN DAN STRATEGI PEMASARAN: ANALISIS LITERATUR REVIEW - Ilyas, Krisna; Hasmin, Farhana; Trisnawataty, Trisnawataty; Indah Safitri, Ari Sarwo; Indah Azhari, Sri Rahayu (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
Social media has fundamentally transformed the landscape of consumer behavior and marketing strategies in the digital era. This research analyzes the influence of social media on consumer behavior transformation and marketing strategy evolution through comprehensive literature review methodology. Analysis reveals that consumer decision journey has evolved from traditional linear models into dynamic and multi-touchpoint processes, where consumers actively conduct in-depth research through user-generated content and social proof before making purchase decisions. Social media creates new paradigms in marketing communication that are interactive and community-based, with user-generated content and peer recommendations becoming dominant factors in shaping brand perception. From strategic perspectives, authentic content marketing, long-term influencer partnerships, and social commerce integration prove most effective in driving customer engagement and conversion. Personalization through advanced targeting and machine learning algorithms enables precision marketing that significantly increases ROI. However, challenges such as privacy concerns, algorithm changes, and competition intensity demand continuous strategic adaptations. Omnichannel integration and advanced analytics become essential for optimizing customer experience and measuring effectiveness of social media marketing investments in achieving business objectives.